2022
DOI: 10.1088/1674-1056/ac6499
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal coupling induced entanglement enhancement in a double-cavity optomechanical system

Abstract: We investigate the quantum entanglement in a double-cavity optomechanical system consisting of an optomechanical cavity and an auxiliary cavity, where the optomechanical cavity mode couples with the mechanical mode via radiation-pressure interaction, and simultaneously couples with the auxiliary cavity mode via nonreciprocal coupling. We study the entanglement between the mechanical oscillator and the cavity modes when the two cavities are reciprocally or nonreciprocally coupled. The logarithmic negativity $E_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Hybrid optomechanical systems, which integrate the advantages of several systems, have become a field of interest. [34][35][36][37][38][39] In this paper, we theoretically study a hybrid optomechanical system consisting of a neutral atom and a nanoparticle levitated in an optical cavity (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid optomechanical systems, which integrate the advantages of several systems, have become a field of interest. [34][35][36][37][38][39] In this paper, we theoretically study a hybrid optomechanical system consisting of a neutral atom and a nanoparticle levitated in an optical cavity (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Yang et al demonstrated the enhancement of nonreciprocal quantum synchronization with strong isolation in antiferromagnet-cavity systems [31]. In addition, exploiting analytical theories and numerical simulations, it is found that compared with ferromagnetic resonance technology, antiferromagnetic resonance technologies should be more suitable for finding inherent inertial spin dynamics on ultrafast time scales [32].…”
mentioning
confidence: 99%